EFFECT OF SUBLETHAL CONCENTRATION OF DIMECRON (ORGANOPHOSPHATE) ON TOTAL PROTEIN AND TOTAL AMINO ACID CONTENT IN OVARIES OF FRESHWATER FISHES BARLIUS BENDELISIS AND BARLIUS BURNA - S. M. KAMBLE; S. D. TAPASE; R. M. SHAMBHARKAR (The Bioscan, 2011)
The total protein and total amino acid content of ovaries were studied in the freshwater fish; Barilius bendelisis and Barilius burna exposure to various sublethal concentrations of Dimecron (0.0064%, 0.0128%, 0.0192 and 0.0075%, 0.015%, 0.0225%) respectively for different time periods up to 96 hrs. All the concentrations of Dimecron brought about a significantly decrease in total protein and total amino acid content. The results are discussed in relation to the concentration of the most commonly used pesticide in this region.